Вплив нітропрусиду натрію у букальній лікарській формі на персистенцію нейрогуморальних маркерів дисфункції ендотелію та функціональної активності тромбоцитів у хворих на артеріальну гіпертензію з неускладненими гіпертензивними церебральними і кардіальними кризами - Кечин, Ігор Леонідович; Візір, Вадим Анатолійович; Нагорний, Володимир Володимирович (My University, 2009)
Натрия нитропрусид в форме букальных пленок «Нипруцел» уменьшает агрегацию тромбоцитов на фоне снижения содержания фибриногена у больных с церебральными и кардиальными гипертензивными кризами. При кардиальных кризах «Нипруцел» достоверно увеличивает время достижения максимальной агрегации, что свидетельствует о дезагрегационном действии исследованной лекарственной формы натрия нитропрусида. На основе этих данных можно рекомендовать применение «Нипруцела» у больных артериальной гипертензией при развитии кардиальных и церебральных гипертонических кризов с целью улучшения реологических свойств крови. Summary. Sodium nitroprusid in the form of buccal membranes «Niprucel» reduces aggregation of thrombocytes on a background of depression of the maintenance of fibrinogen in patients with cerebral and cardial hypertensive crisises. In cardial crisises « Niprucel » authentically enlarges time of achievement of the maximal aggregation; this testifies to desaggregation action of the investigated medicinal form of sodium nitroprusid. On the basis of these data it is possible to recommend application of «Niprucel» in development of cardial and cerebral hypertonic crisises with the purpose to improve rheologic properties of blood to patients with arterial hypertensia.
Keywords: артеріальна гіпертензія; кардіальний криз; церебральний криз; натрію нітропрусид; плівки букальні; arterial hypertensia; cardial crisis; cerebral crisis; sodium nitroprusid; membranulas bucalis